Pengembangan Media Pembelajaran Berbasis Visualisasi Gua Peninggalan Jepang di Kupang Untuk Meningkatkan Kesadaran Sejarah Siswa - Kollo, Moses; Boimau, Sanhedri (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
The purpose of this study is to find out (1) The use of media in learning history that has been taking place in the XI class of Sudirman Kupang Senior High School so far; (2) historical awareness of class XI Sudirman Kupang high school students; (3) Development of historical learning media based on the Japanese Cave Visualization in Kupang to increase historical awareness of class XI students at Sudirman Kupang High School; and (4) Effectiveness of the application of the Japanese Cave Visualization Media in Kupang in history learning in class XI of Sudirman Kupang High School. This research was conducted at Sudirman Kupang High School. This research is a research or development called research and development (R & D). The results showed that (1) the use of media in history learning that took place so far in class XI of Sudirman Kupang high school was still said to be minimal; (2) after learning in the classroom using the Kupang Japan cave visualization media, class XI students at Sudirman Kupang High School felt it was important to visit the Kupang Japan cave site; (3 development of historical learning media based on visualization of Japanese caves in Kupang was carried out through several stages including (a) the stage of material selection ie the researcher chooses the subject used in the development activity; c) producing a learning video, at this stage, the researcher utilizes Adobe photo shop CC 2015 software, Vegas pro 13, Adobe After Affact and Adobe Audition, (d) product validation.After validating the expert both material and media, the resulting product is declared (4) learning media based on Kupang Japan cave visualization is very effective in increasing the historical awareness of class XI students of Sudirman Kupang High School.